Capacidade para o trabalho e produtividade de pessoas com úlcera venosa - Faria, Elaine Cristina [UNIFESP] (2017)
Background: Work ability is influenced by multiple factors, such as the presence of morbidities as venous ulcers, which may lead to its decline. Objective: To assess work ability and productivity in individuals with venous ulcers. Methods: This multicenter study was conducted with 300 participants of both genders, with a mean age of 46.3 years, who were divided into three groups: the control group, venous insufficiency (VI) group, and venous ulcer (VU) group. Sociodemographic characteristics of patients were recorded and the Brazilian-Portuguese versions of the Work Ability Index (WAI), Work Productivity and Activity Impairment - General Health (WPAI-GH) questionnaire, and Work Limitations Questionnaire (WLQ) were applied to all subjects. Results: The mean WAI value was significantly lower in the VU group than in the VI group (p<0.001). Mean WAI values in the VU and VI groups were respectively 20.6 and 8.2 points lower compared to the control group. Patients in the VU group reported higher WLQ index and scores on all domains than those in the VI group (p<0.001); 0.28 points higher on absenteeism than controls; and higher presenteeism (p<0.001), higher absenteeism+presenteism (p=0.004) and greater impairment (p=0.004) when compared with patients in the VI group. Conclusion: Venous ulcer reduced the work ability and productivity of patients, leading to increased presenteeism and absenteeism.